Serum metabolic profiles in quails: Effects of age, breed, and sex - Qin He; Hanle Shang; Yizhong Huang; Lizhi Li; Zhuomin Wu; Huihui Ran; Jiguo Xu; Xinwei Xiong (Poultry Science)
Over the past decade, metabolomic research in livestock and poultry has gained considerable momentum; however, quail metabolomics still lags behind that of livestock species such as chickens, pigs, and cattle. Quails are important models due to their low-cost protein sources—both eggs and meat—and practical benefits such as minimal space requirements, high egg production, disease resistance, and rapid reproduction. Therefore, it is necessary to systematically understand the effects of various factors on quail metabolism to provide a theoretical basis for accurate feeding and breeding practices. In this study, liquid chromatography with tandem mass spectroscopy (LC-MS/MS)-based metabolomics was used to examine the effects of age, breed, and sex on the serum metabolic profile of quails. A total of 550 metabolites were identified. Relative to breed and sex, we found that age played a crucial role in influencing quail serum metabolites. At 20 days of age (D20), quails had high levels of serum thymidine and alpha-D-glucose, while at 70 days of age (D70), the lipids, including 3-isothujone, 15-deoxy-d-12,14-PGJ2, and 2-aminobut-2-enoate dominated the serum. Additionally, xanthine, hypoxanthine, diaminopimelic acid, and 2-deoxy-scyllo-inosose appeared to be specific metabolites of Japanese quail (JAPQ). Serum levels of N-acetylglutamic acid, hydroxypyruvic acid, carnosine, alloepipregnanolone, lumichrome, 6-hydroxynicotinate, and myristic acid were higher in D70 Hengyan white feather quails (HYWQ) than those in D70 JAPQ. Notably, this study also identified 2-hydroxy-2-ethylsuccinic acid and riboflavin as potential specific metabolites in female quails. Furthermore, integration analysis showed that amino acid biosynthesis and metabolism, as well as ABC transporters, were the key pathways distinguishing D20 from D70. Purine metabolism, pyrimidine metabolism, ABC transporters, and TCA cycle were the key pathways distinguishing HYWQ from JAPQ. Differences in energy metabolism and amino acid biosynthesis and metabolism were observed between males and females. These findings enhance our understanding of the dynamic changes in quail serum metabolites influenced by various factors and address the knowledge gap regarding serum metabolic changes at different stages in quails.